Resuscitative endovascular occlusion of the aorta (REBOA) for refractory out of hospital cardiac arrest. An Utstein-based case series. (August 2021) - Gamberini, Lorenzo; Coniglio, Carlo; Lupi, Cristian; Tartaglione, Marco; Mazzoli, Carlo Alberto; Baldazzi, Marzia; Cecchi, Alessandra; Ferri, Enrico; Chiarini, Valentina; Semeraro, Federico; Gordini, Giovanni; ,
Abstract: Aims: Out of hospital cardiac arrest (OHCA) is still a leading cause of mortality worldwide. In recent years, resuscitative endovascular balloon occlusion of the aorta (REBOA) has been progressively studied as an adjunct to standard advanced life support (ALS) in both traumatic and non-traumatic refractory OHCA. Since January 2019, the REBOA procedure has been applied to all the patients experiencing both traumatic and non-traumatic refractory OHCA (≥15 min of cardiopulmonary resuscitation) not eligible for ECPR for clinical or logistic reasons. We aimed at describing the feasibility and effects of REBOA performed both in the Emergency Department and in the pre-hospital environment served by the local HEMS for refractory OHCA. Methods: Twenty consecutive patients experiencing refractory OHCA and in whom REBOA was attempted in 2019 and 2020 were included in the study, Utstein data and REBOA specific variables were recorded. Results: Successful catheter placement was achieved in 18 out of 20 patients, 11 of these were non-traumatic OHCAs while 7 were traumatic OHCAs, the 2 failures were related to repeated arterial puncture failure. Median time between the EMS dispatch and REBOA catheter placing attempt was 46 min. An increase in etCO2 over 10 mmHg was observed after balloon inflation in 12 out of 18 patients (8/11 non-traumatic and 4/7 traumatic OHCAs), a sustained ROSC was observed in 5 patients (1 traumatic and 4 non-traumatic OHCA) that were subsequently admitted to the ICU. Four out of the 5 patients reached the criteria for brain death in the subsequent 24 h while one patient experienced another episode of refractory cardiac arrest in ICU and subsequently died. Conclusion: Our data confirm the feasibility of REBOA technique as an adjunct to ALS in both the ED and prehospital phase and most of the treated patients experienced a transient ROSC after balloon inflation while 5 out of 18 experienced a sustained ROSC. However, while in the trauma setting increasing evidence suggests an improved survival when REBOA is applied to refractory OHCA, in non-traumatic OHCA this has yet to be demonstrated and large studies are needed.